Family Presence in the Intensive Care Unit and Emergency Department: A Metasynthesis. Issue 2 (June 2017) - Cypress, Brigitte S.; Frederickson, Keville
Abstract: Few findings from qualitative studies about family presence in intensive care units (ICU) and emergency departments (ED) have been synthesized, despite a renewed appreciation and interest in incorporating qualitative studies in systematic reviews of evidence‐based practice. We synthesized findings from 17 qualitative studies on family presence and the experiences of patients, families, and nurses. The essential themes of emotional support, feelings of safety and comfort, knowing, understanding, being informed, and being engaged emerged from the review synthesis. An overarching theme of family coping during stressful times, such as hospitalization, is described as system support and noted in the literature as a component of family resilience. We recommend that further studies be conducted to relate supportive behaviors of critical care nurses to family functioning and provide empirical evidence for further development of the theory of family resilience.